Identity crisis facing Islamic literature - Zulkarnain Mohamed (Penerbit Universiti Kebangsaan Malaysia, 2000)
This article is aimed at examining challenges in literary arena against the advancement of Islamic literature. It attempts to solve the problem of identifying the position of Islamic literature in the face of the mainstream of Western literature. The main objective of the article is to prove the shifting paradigm of Islamic literature. Several points include confusions over Islamic literature, comparison between two distinctive eras of every Islamic literary activity that consist of the Classical time, i.e., the early Islamic period up to the epoch of Islamic civilization and the modern time. The article is written to examine the development of present literary activities of Islam and non-Islam. This is to explore the differences and similarities that might arise from the literary activities and necessitate the present Islamic literature to be reviewed so that it conforms to Islamic teachings. In other words, this article attempts to put forward a new identity for Islamic literature in line with the spirit of Islam and the need of modern time